Dissection of Insertion–Deletion Variants within Differentially Expressed Genes Involved in Wood Formation in Populus - Gong, Chenrui; Du, Qingzhang; Xie, Jianbo; Quan, Mingyang; Chen, Beibei; Zhang, Deqiang (Frontiers in Plant Science, 2018)
Short insertions and deletions (InDels) are one of the major genetic variants and are distributed widely across the genome; however few investigations of InDels have been conducted in long-lived perennial plants. Here, we employed a combination of RNA-seq and population resequencing to identify InDels within differentially-expressed genes underlying wood formation in a natural population of Populus tomentosa (435 individuals) and utilized InDel-based association mapping to detect the causal variants under additive, dominance, and epistasis underlying growth and wood properties. In the present paper, 5,482 InDels detected from 629 differentially expressed (DE) genes showed uneven distributions throughout all 19 chromosomes, and 95.9% of these loci were diallelic InDels. 74 InDels (FDR q≤ 0.10) from 68 genes exhibited significant additive/dominant effects on ten growth and wood-properties, with an average of 14.7% phenotypic variance explained. Potential pleiotropy was observed in one-third of the InDels (representing 24 genes). Seven genes exhibited significantly differential expression among the genotypic classes of associated InDels, indicating possible important roles for these InDels. Epistasis analysis showed that overlapping interacting genes formed unique interconnected networks for each trait, supporting the putative biochemical links that control quantitative traits. Therefore, the identification and utilization of InDels in trees will be recognized as an effective marker system for molecular marker-assisted breeding applications, and further facilitate our understanding of quantitative genomics.